Influence of pH value on properties of YPO4：Tb3＋ phosphor by co-precipitation method - 李旭 王皓岩 关丽 付跃举 郭镇 袁坤生 铁利成 杨志平 滕枫 (Journal of rare earths, 2015)
A series of Y1_xPO4：xTb3＋ （x=0.005-0.1） phosphors were successfully fabricated by using co-precipitation method with NHzH2PO4 as phosphorus source. The structure and morphology characterization of the luminescent material was investigated with X-ray powder diffraction （XRD） and field emission scanning electron microscopy （FESEM）. The XRD patterns indicated that the samples belonged to tetragonal phase. Luminescence properties were discussed by measuring the excitation and emission spectra. The phosphor could be excited by UV light （340-390 nm） and emitted green light, with the emission peaks located at 491 （5Da→7F6）, 550 （SD4→7Fs）, 589 （5D4→7F4） and 624 nm （SD4→TF3）. In addition, the pH value and activator concentration had great effects on the emission intensity. The results illuminated that this phosphor could be used for UV based white light emitting diodes and co-precipitation method could be used to prepare better appearance phosphor.